Contribution of Dr. Israr Ahmed in the interpretation of Quran (As a Mudarris and Mufassir ) - Muhammad Ramzan Arien (The Islamic Culture, 2019)
Dr. Israr Ahmed (late) was Pakistani Islamic Scholar and Philosopher. He Launch vigorous movement for the revival of Islam. He was founder of Markazi Anjuman Khuddam-ul-Quran Lahore, Tanzeem-e-Islami Pakistan and Tahreek-e-Khalifat Pakistan. He also started a social movement of marital simplicity. He wrote above than 70 books on different aspects of Islam and religion, and some of them were translated into English and other languages. Dr. Israr Ahmed presented Quranic Teaching in Scientific and enlightened (different) way. He was awarded Sitara-e-Imtiaz in 1981. He criticized modern democracy and prevalent electoral system and argued that the head of an Islamic state could reject the majority decisions. He wanted implementation of Islamic system in Social, Cultural, Juristic, Political and economic field.